2022
DOI: 10.54314/jssr.v5i3.994
|View full text |Cite
|
Sign up to set email alerts
|

Komparasi Random Forest Dan Logistic Regression Dalam Klasifikasi Penderita Covid-19 Berdasarkan Gejalanya

Abstract: In data mining, we can use symptoms suffered by patients for a reference in classifying positive and negative Covid-19 patients using data mining. Random Forest and logistic regression are two data mining algorithms with high accuracy, precision, and sensitivity in data classification. This study compares the random forest and the logistic regression algorithm - where we use the lasso and ridge regulations - on classifying positive and negative Covid-19 patients based on their symptoms. From 5434 data used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Logistic regression was chosen as a combination of the VGG-19 because this algorithm has high flexibility, especially in the regularization selection, such as lasso and ridge [9]. Several studies have shown the effect of the lasso and ridge regularization in various Logistic regression classifications: in the COVID-19 patient classification , the lasso regularization performs better than the ridge [14]; in the breast cancer classification, the ridge regularization performs better than the lasso regularization [15]; and research C. This research uses the VGG-19 to transfer the feature extraction into the Logistic regression algorithm's dataset for classifying the feral cat images. We compare the accuracy, precision, and recall from each of the six models after combining lasso and ridge regularization with different cost parameter values.…”
Section: Imentioning
confidence: 99%
“…Logistic regression was chosen as a combination of the VGG-19 because this algorithm has high flexibility, especially in the regularization selection, such as lasso and ridge [9]. Several studies have shown the effect of the lasso and ridge regularization in various Logistic regression classifications: in the COVID-19 patient classification , the lasso regularization performs better than the ridge [14]; in the breast cancer classification, the ridge regularization performs better than the lasso regularization [15]; and research C. This research uses the VGG-19 to transfer the feature extraction into the Logistic regression algorithm's dataset for classifying the feral cat images. We compare the accuracy, precision, and recall from each of the six models after combining lasso and ridge regularization with different cost parameter values.…”
Section: Imentioning
confidence: 99%
“…AdaBoost is an algorithm that trains a classifier by selecting crucial features from weak classifier linear combinations [25]. The formulas in equations ( 6) to (8) show the calculation to evaluate a model's performance using the accuracy, precision, and recall values [26]. AdaBoost uses the combination of ht(x) (a based classifier), αt (a learning rate), and F(x) (a strong classifier) in the formula, as shown in equation (2).…”
Section: Adaboostmentioning
confidence: 99%
“…Using flood incidents and water level data from DKI Jakarta as a source of knowledge, data mining is a suitable tool to categorize the flood status by classifying the data into specified categories [3]. Data mining analyzes and extracts knowledge from a dataset and uses that knowledge to solve problems such as association, clustering, prediction, estimation, and classification [4]. Some popular data mining algorithms used in classification problems are K-nearest neighbors (K-NN), support vector machine (SVM), and naive Bayes (NB) for their high processing speed, easy implementation, and good performance [5].…”
Section: Imentioning
confidence: 99%